Climate mitigation by dairy intensification depends on intensive use of spared grassland. (21st September 2017) - Styles, David; Gonzalez‐Mejia, Alejandra; Moorby, Jon; Foskolos, Andreas; Gibbons, James
Abstract: Milk and beef production cause 9% of global greenhouse gas (GHG) emissions. Previous life cycle assessment (LCA) studies have shown that dairy intensification reduces the carbon footprint of milk by increasing animal productivity and feed conversion efficiency. None of these studies simultaneously evaluated indirect GHG effects incurred via teleconnections with expansion of feed crop production and replacement suckler‐beef production. We applied consequential LCA to incorporate these effects into GHG mitigation calculations for intensification scenarios among grazing‐based dairy farms in an industrialized country (UK), in which milk production shifts from average to intensive farm typologies, involving higher milk yields per cow and more maize and concentrate feed in cattle diets. Attributional LCA indicated a reduction of up to 0.10 kg CO2 e kg −1 milk following intensification, reflecting improved feed conversion efficiency. However, consequential LCA indicated that land use change associated with increased demand for maize and concentrate feed, plus additional suckler‐beef production to replace reduced dairy‐beef output, significantly increased GHG emissions following intensification. International displacement of replacement suckler‐beef production to the "global beef frontier" in Brazil resulted in small GHG savings for the UK GHG inventory, but contributed to a net increase in international GHG emissions equivalent to 0.63 kg CO2 e kg −1 milk. Use of spared dairy grassland for intensive beef production can lead to net GHG mitigation by replacing extensive beef production, enabling afforestation on larger areas of lower quality grassland, or by avoiding expansion of international (Brazilian) beef production. We recommend that LCA boundaries are expanded when evaluating livestock intensification pathways, to avoid potentially misleading conclusions being drawn from "snapshot" carbon footprints. We conclude that dairy intensification in industrialized countries can lead to significant international carbon leakage, and only achieves GHG mitigation when spared dairy grassland is used to intensify beef production, freeing up larger areas for afforestation. Abstract : Previous studies have shown that the carbon footprint of milk declines as dairy farming intensifies, owing to improved feed conversion efficiency. For the first time, we demonstrate that direct greenhouse gas (GHG) mitigation achieved by intensification of UK dairy farms is outweighed by GHG emissions from land use change driven by increased demand for maize and concentrate feed, plus additional suckler‐beef production required to replace reduced dairy‐beef output. Dairy intensification can cause international carbon leakage, and may only achieve net GHG mitigation when spared dairy grassland is used to intensify beef production, freeing up larger areas for afforestation